Changes of Comfort Parameters and Test Day Milk Yield in Holstein Cows - Aksu, Coskun; Atasever, Savas (University of Agricultural Sciences & Veterinary Medicine Bucharest, 2017)
The objective of this investigation was to reveal the changes of comfort parameters and test day milk (TDMY) according to environmental factors in Holstein cows. In total, 99 clinically healthy cows reared at a private farm in the Black Sea region of Turkey were examined. Flank hygiene (FH), rear legs hygiene (RLH), body condition score (BCS) and rumen fill (RF) were selected as comfort parameters and tested in two seasons (spring and summer), parity (first and second) and stage of lactation (<200 d and >= 200 d) groups by t-test. While season affected all comfort parameters and TDMY (P<0.001), stage of lactation only affected BCS (P<0.001) and RF (P<0.05). The cows with second parity had higher milk production (P<0.05). Moderate correlation coefficients were determined between FH and RLH (r= 0.557; P<0.01) or between BCS and RF (r= 0.525; P<0.01).
Keywords: Comfort; Cow; Hygiene; Milk Production